Festival Pint of Science and Cultural Inclusion: Science in Bar Talk - Ferracioli, Laércio; Krohling, Werther; Souza Salgado, Breno; Buaiz, Angela (Guará Journal, 2019)
The Pint of Science Festival is a science outreach and communication event for citizens interested in the results of scientific and technological research and their impact on daily life. Pint of Science is a science culture event that provides public accountability for public investments and provides citizens with objective knowledge so they can make transformative decisions based on rational and realistic premises to improve living conditions. The event began in England in 2012 and reached a global scale in 2018, being held simultaneously over three days in 21 countries and 56 Brazilian cities. This article reports on the first Pint of Science Festival in Vitória, Espírito Santo, on May 14, 15, and 16, 2018. The results reveal a strongly positive evaluation by the public, who presented suggestions and criticisms for its continuation in 2019.